INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) - Montero, G; TORRES, E; Suárez, M A; Ortega, C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied
Keywords: cork-oak; silviculture; stand density

LIMITACIONES A LA REGENERACIÓN NATURAL DE LOS ALCORNOCALES EN EL PARQUE NACIONAL DE DOÑANA (HUELVA, ESPAÑA) P.M. - VÁZQUEZ, P M; Suárez, M A; TORRES, E (II Congreso Forestal Español, 1977)
The possible limitations to the in several experiences natural regeneration of the Quercus suber L. in a guarded area (Doñana) are undertaken in this study. The outputs offer a global vision of the natural regeneration in the Doñana's National Park. The production of seeds the sanitary state of the hoisted and their plagues, the attack of the spineless on the fruits and the climate don't harm the process of the natural regeneration in the -forest of Q. suber L. However the animal pressure (mammals), and the load cattle are the two factor s that impede the natural regeneration of the cork oak in Doñana. Finally, different strategies are contributed in order to recuperate the cork oak: fence, sowing, plantation and descent of the pressure animal in the zone.
Keywords: cork-oak; Doñana; natural regeneration; Quercus suber L.; silviculture